De novo biosynthesis of garbanzol and fustin in Streptomyces albus based on a potential flavanone 3‐hydroxylase with 2‐hydroxylase side activity. Issue 5 (3rd July 2021) - Marín, Laura; Gutiérrez‐del‐Río, Ignacio; Villar, Claudio Jesús; Lombó, Felipe
Summary: Flavonoids are important plant secondary metabolites, which were shown to have antioxidant, anti‐inflammatory or antiviral activities. Heterologous production of flavonoids in engineered microbial cell factories is an interesting alternative to their purification from plant material representing the natural source. The use of engineered bacteria allows to produce specific compounds, independent of soil, climatic or other plant‐associated production parameters. The initial objective of this study was to achieve an engineered production of two interesting flavanonols, garbanzol and fustin, using Streptomyces albus as the production host. Unexpectedly, the engineered strain produced several flavones and flavonols in the absence of the additional expression of a flavone synthase (FNS) or flavonol synthase (FLS) gene. It turned out that the heterologous flavanone 3‐hydroxylase (F3H) has a 2‐hydroxylase side activity, which explains the observed production of 7, 4′‐dihydroxyflavone, resokaempferol, kaempferol and apigenin, as well as the biosynthesis of the extremely rare 2‐hydroxylated intermediates 2‐hydroxyliquiritigenin, 2‐hydroxynaringenin and probably licodione. Other related metabolites, such as quercetin, dihydroquercetin and eriodictyol, have also been detected in culture extracts of this recombinant strain. Hence, the enzymatic versatility of S. albus can be conveniently exploited for the heterologous production of a large diversity of plant metabolites of the flavonoid family. Abstract : The heterologous production of different plant flavanones, flavanonols and flavonols has been achieved in the Streptomyces albus bacteria, including several rare 2‐hydroxy flavonoids harboring unusual hemiacetal moieties, and sheds light in the potential bifunctional enzymatic activity for F3H hydroxylase.